“Door-In to Door-Out” Delay in Patients with Acute ST-Segment Elevation Myocardial Infarction Transferred for Primary Percutaneous Coronary Intervention in a Metropolitan STEMI Network of a Developing Country - Dakota, Iwan; Dharma, Surya; Andriantoro, Hananto; Firdaus, Isman; Danny, Siska Suridanda; Zamroni, Dian; Radi, Basuni (International Journal of Angiology, 2020)
Routine performance measures of primary percutaneous coronary intervention (PCI) within an ST-segment elevation myocardial infarction (STEMI) network are needed to improve care.We evaluated the door-in to door-out (DI–DO) delays at the initial hospitals in STEMI patients as a routine performance measure of the metropolitan STEMI network.We retrospectively analyzed the DI–DO time from 1,076 patients with acute STEMI who were transferred by ground ambulance to a primary PCI center for primary PCI between 4 October 2014 and 1 April 2019. Correlation analysis between DI–DO times and total ischemia time was performed using Spearman's test. Logistic regression analyses were used to find variables associated with a longer DI–DO time.Median DI–DO time was 180 minutes (25th percentile to 75th percentile: 120–252 minutes). DI–DO time showed a positive correlation with total ischemia time (r = 0.4, p < 0.001). The median door-to-device time at the PCI center was 70 minutes (25th percentile to 75th percentile: 58–88 minutes). Multivariate analysis showed that women patients were independently associated with DI–DO time > 120 minutes (odds ratio 1.55, 95% confidence interval 1.03 to 2.33, p = 0.03).The DI–DO time reported in this study has not reached the guideline recommendation. To improve the overall performance of primary PCI in the region, interventions aimed at improving the DI–DO time at the initial hospitals and specific threat for women patients with STEMI are possibly the best efforts in improving the total ischemia time.
Keywords: DI–DO; STEMI care; primary PCI